Preparation of Low Fat Lassi by Incorporation of Ginger (Zingiber officinale L.) Juice - Raje-Nimbalkar, F. A.; Patil, V. N.; Raskar, A. B.; Kadav, V. B.; Joshi, S. V. (International Journal of Bio-resource and Stress Management, 2023)
The study was conducted at Dept. of Animal Husbandry and Dairy Science, Dr. BSKKV, Dapoli, Ratnagiri, Maharashtra, India during August 2010–January 2011 to evaluate the suitability of ginger juice as flavoring agent in developing ginger lassi. Lassi is a cultured milk beverage and a popular product in India, In Maharashtra also generally lassi is prepared from buffalo milk curd which gives creamy appearance with pleasant mildly acidic sweet taste and rich aroma. The functionality of Lassi increases with the addition of probiotic microorganisms and incorporation of antioxidant rich fruit juice provides strong antioxidant power endow with value addition to the finished product. Ginger is mostly used to cure nausea, ulcer, stroke, Sore throat, Hypertension, indigestion, and Arthritis. Ginger appears to be promising for safe use in medicine, pharmaceutical and food industries. Ginger is a popular home remedy in India today. Hence forth considering the medicinal properties of ginger and use of skim milk in restricting the caloric intake. The lassi was prepared from buffalo skim milk by using ginger juice at different levels viz. 1.5% (T1), 3.0% (T2), 4.5% (T3) and 6.0% (T4) of the content. This prepared lassi was compared with control lassi (T0) i.e. without addition of ginger juice. Ginger juice could be successfully utilized for preparation of herbal lassi. The most acceptable quality lassi can be prepared by using 3.0% ginger juice and It recorded on an average total solid, fat, protein, ash, and acidity as 18.49, 0.52, 3.43, 0.78, and 0.79% respectively.